Síntese e caracterização de zeólitas ZSM-5 por diferentes rotas e seu emprego na produção de olefinas leves a partir de etanol - Salbego, Paulo Roberto dos Santos (2014)
This work aims the synthesis and study of ZSM-5 catalysts for the conversion of ethanol to light olefins, especially, using an alternative and inexpensive route. The ethanol emerges as a renewable source for the production of olefins and the ZSM-5 catalyst has important characteristics for this type of reaction such as acidity, surface area and particle size. The synthesis was carried out in hydrothermal treatment at 170 °C. Were performed two conventional synthesis with templates, using n-Butylamine and tetrapropylammonium hydroxide (TPAOH), and an third and alternative route using a nucleating gel. The catalyst characterization was performed using several techniques (XRD, BET, XRF, SEM and TGA) and was observed the formation of the ZSM-5 structure in all the synthesis methods. The catalysts were evaluated in the ethanol to olefins (ETO) reaction, and was evaluated the influence of the reaction temperature (250 to 450 °C) and SAR (SiO2/Al2O2 ratio) in the selectivity for olefins. The products analyses were made with a gas chromatograph with a FID-type detector. The ethylene yield was above to 80 % for all catalysts, and some above 90 %. Lower SAR values provided higher yields for propylene, around to 9 %. The temperature, SAR and template used in the synthesis influenced in the selectivity. In addition, was evaluated the influence of the catalyst mass, dilution and also its modification with different metals. When the mass was increase, the yield for propylene increased. The catalyst dilution with common sand provided, in some concentrations, greater propylene formation. The nucleating gel method showed to be a viable alternative for ZSM-5 synthesis and its use in the ETO reaction.